Strategi Membangun Kepercayaan terhadap Lembaga Kepolisian melalui Pendekatan Sosio Institusional Komperatif - Muhtadin, Muhtadin (Lembaga Yasin AlSys, 2022)
The police need the public's trust to do their job well. Recognizing this, police organizations across Europe are applying a variety of methods to gain trust or trust-building strategies. In its implementation, trust in the police and the legitimacy of the police pay less attention to what the police do to increase trust. In this regard the author will outline an approach to understanding strategies for building police trust in their social and institutional contexts by applying a comparative and dynamic perspective. Illustrating the value of a socio-institutional approach to trust-building strategies, each of these phases is discussed in the context of a comparative and dynamic study of police trust building strategies in England and Wales, Denmark, and the Netherlands. It is said that a more sophisticated understanding of building trust in its social and institutional context not only tells us something about the police, but also helps us understand how state institutions shape and maintain their position in the complex environment of our changing society.